IMPLEMENTATION OF WORKSHOP ACTIVITIES TO IMPROVE TEACHER COMPETENCY IN DEVELOPING LESSON PLANS - Sargiono Sargiono (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This research was conducted at SDN 017 Candirejo, Pasir Penyu District with 15 teachers. This study aims to improve teacher competency in Developing Lesson Plans (RPP) by implementing workshop activities. The type of the research was action research. This research procedure was carried out in two cycles, and the steps in each cycle consisted of planning, implementing actions, observing, and reflecting. The results showed that before giving an average action, the teacher got a value of 74.4 with sufficient qualifications, then after taking action in the first cycle, the average teacher got a score of 81 with good qualifications. In the second cycle, the average teacher's assessment increased to 86.7 with very good qualifications. The percentage increased from the pre-action to the first cycle was 6.6% and the pre-action to the second cycle was 12.3%. It can be concluded that the implementation of the workshop activities can improve teacher competency in preparing RPP at SDN 017 Candirejo, Pasir Penyu District.